Dissolved and particulate organic carbon in hydrothermal plumes from the East Pacific Rise, 9 degrees 50′N - Bennett, S A; Statham, P J; Green, D R H; Le Bris, N; McDermott, J M; Prado, F; Rouxel, O J; Von Damm, K L; German, C R (Deep-Sea Research. Part I: Oceanographic Research Papers, 2011)
Chemoautotrophic production in seafloor hydrothermal systems has the potential to provide an important source of organic carbon that is exported to the surrounding deep-ocean. While hydrothermal plumes may export carbon, entrained from chimney walls and biologically rich diffuse flow areas, away from sites of venting they also have the potential to provide an environment for in-situ carbon fixation. In this study, we have followed the fate of dissolved and particulate organic carbon (DOC and POC) as it is dispersed through and settles beneath a hydrothermal plume system at 9°50′N on the East Pacific Rise. Concentrations of both DOC and POC are elevated in buoyant plume samples that were collected directly above sites of active venting using both DSV Alvin and a CTD-rosette. Similar levels of POC enrichment are also observed in the dispersing non-buoyant plume, ∼500 m downstream from the vent-site. Further, sediment-trap samples collected beneath the same dispersing plume system, show evidence for a close coupling between organic carbon and Fe oxyhydroxide fluxes. We propose, therefore, a process that concentrates POC into hydrothermal plumes as they disperse through the deep-ocean. This is most probably the result of some combination of preferential adsorption of organic carbon onto Fe-oxyhydroxides and/or microbial activity that preferentially concentrates organic carbon in association with Fe-oxyhydroxides (e.g. through the microbial oxidation of Fe(II) and Fe sulfides). This potential for biological production and consumption within hydrothermal plumes highlights the importance of a multidisciplinary approach to understanding the role of the carbon cycle in deep-sea hydrothermal systems as well as the role that hydrothermal systems may play in regulating global deep-ocean carbon budgets.
Keywords: HOV Alvin (Human Occupied Vehicle)